A Qualitative Analysis of the Agricultural Policy Dynamics and the Nigerian Economy : 1960-2015 - Igudia, Patrick Ohunmah (European Scientific Journal, ESJ, 2017)
Historically, the agricultural sector constitutes one of the most important sectors of most countries including the highly industrialised ones like the USA, Japan, and England. In Nigeria, agriculture has been the engine of growth of its economy. However, this role has not been optimally exploited by successive administrations to develop strategic growth path for Nigeria as has been achieved by the aforementioned industrialised countries and some emerging ones like China and Brazil. Nigeria has a rich agricultural resource endowment and an avalanche of laudable agricultural policies that could turn her into an industrialised economy and reduce the incidence of poverty. The last in the series of laudable agricultural policies meant to entrench Nigeria’s economic growth within the agricultural framework was the transformation agenda. The agricultural transformation agenda of the last administration (2011-2015) was intended to re-enact once again agriculture as the main driver of Nigeria’s economic growth as in the 1960s and 1970s. Earlier attempts underperformed due principally to the ineffective implementation or complete abandonment of such policies. The result has been a fall in foreign exchange earnings, low GDP level and lack of sectoral linkages. This study made several recommendations including the need for a consistent increase in government budgetary allocation to the sector so as to redress this enigma and bring back the old post-independence glory of the sector.